Identification of translational dermatology research priorities in the U.K.: results of an electronic Delphi exercise. (1st November 2015) - Healy, E.; Brown, S.J.; Langan, S.M.; Nicholls, S.G.; Shams, K.; Reynolds, N.J.; ,; Ardern‐Jones, Mike; Benham, Marilyn; Jaega, Mike; Leigh, Irene; McLean, Irwin; et al.
Summary: Background: Translational research is the direct application of basic and applied research to patient care. It is estimated that there are at least 2000 different skin diseases; thus, there are considerable challenges in seeking to undertake research on each of these disorders. Objectives: This electronic Delphi (e‐Delphi) exercise was conducted in order to generate a list of translational dermatology research questions that are regarded as a priority for further investigations. Methods: During the first phase of the e‐Delphi exercise, 228 research questions were generated by an expert panel that included clinical academic dermatologists, clinical dermatologists, nonclinical scientists, dermatology trainees and representatives from patient support groups. Results: Following completion of the second and third phases, 40 questions on inflammatory skin disease, 20 questions on structural skin disorders/genodermatoses, 37 questions on skin cancer and eight miscellaneous questions were designated as priority translational dermatology research questions (PRQs). In addition to PRQs on a variety of disease areas (including multiple PRQs on psoriasis, eczema, squamous cell carcinoma and melanoma), there were a number of cross‐cutting themes that identified a need to investigate mechanisms/pathogenesis of disease and the necessity to improve treatments for patients with skin disease. Conclusions: It is predicted that this list of PRQs will help to provide a strategic direction for translational dermatology research in the U.K. and that addressing this list of questions will ultimately provide clinical benefit for substantial numbers of patients with skin disorders.